Exploration of the Implementation of Learning to Write Procedural Texts and its Implications for Student Learning Outcomes - Redhya, Zulhafizah; Nurbaya, St. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to (1) describe the implementation of learning to write procedural texts, including the use of models, materials, media, and learning evaluation; and (2) describe student learning outcomes related to the use of these models, materials, media, and evaluations. This research is qualitative with an exploratory study design, involving teachers and seventh-grade students at three junior high schools in Yogyakarta. Data collection techniques include observation, interviews, document analysis, and literature study, with data analysis through reduction, modeling, and drawing conclusions. The research results show that two learning models are used, namely project-based learning and problem-based learning. Some teaching materials follow textbooks, while others are developed based on local culture. The media used are varied, including visual, audio-visual, and internet-based media. Learning evaluation uses attitudinal, formative, and summative assessments. The use of project-based learning and audio-visual media is more effective in increasing student motivation, creativity, and learning outcomes.